A new variational line tension model for accurate evaluation of the stress effect on cross-slip energy barrier in face-centered cubic metals. (June 2019) - Liu, Hui; Zhou, Xiao; Hu, Dianyin; Song, Jun; Wang, Rongqiao; Mao, Jianxing
Abstract: The present work developed a new variational line tension model (LTM) that accounts for contributions from the local line energy, long-range interaction among dislocation segments, and interplay between dissociated partials. This new LTM has been shown to accurately predict cross-slip energy barriers under different stress states, verified through atomistic simulations on the face-centered cubic (FCC) nickel model system. We demonstrated that the line tension in general is not a constant, but varies with the local dislocation length and the separation distance between dissociated dislocations, and thus the constant line tension assumption is inherently inadequate. Graphical abstract: Unlabelled Image